Physical modelling to demonstrate the feasibility of screw piles for offshore jacket-supported wind energy structures. Issue 2 (27th February 2022) - Davidson, Craig; Brown, Michael John; Cerfontaine, Benjamin; Al-Baghdadi, Therar; Knappett, Jonathan; Brennan, Andrew; Augarde, Charles; Coombs, William; Wang, Lei; Blake, Anthony; Richards, David; Ball, Jonathan David
Abstract : Screw piles potentially offer quieter installation and enhanced axial tensile capacity over straight-shafted driven piles. As such, they have been suggested as a possible foundation solution for offshore jacket-supported wind turbines in deeper water. To investigate the feasibility of their use in this setting, centrifuge testing of six model screw piles of different designs was conducted to measure the installation requirements and ultimate axial capacity of the piles in very dense and medium-dense sand. The screw piles were designed to sustain loads generated by an extreme design scenario using published axial capacity and torque prediction formulae. Single- and double-helix designs, including an optimised design, intended to minimise installation requirements, with reduced geometry were installed and tested in-flight. Piles in the medium-dense sand, for example, had significant installation requirements of up to 18·4 MNm (torque) and 28·8 MN (vertical force), which were accurately predicted using correlations with cone resistance data (cone penetration test). Existing axial capacity design methods did not perform well for these large-scale screw piles, overestimating compressive and tensile capacities. Revised analytical methods for installation and axial capacity estimates are proposed here based on the centrifuge test results.